The Correlation Between Low Birth Weight (LBW) And Stunting In 1-5 Years Old Children At Gunungkidul, Yogyakarta, Indonesia - hutasoit, masta (Sahabat Publikasi Kuu, 2024)
Background: Stunting is still a major health problem in children, especially in developing countries including Indonesia. Stunting is a growth disorder with height below -2 standard deviations. One of the factors that cause stunting is low birth weight, which is <2500 grams. Stunting can affect the quality of human resources in the future because it can hinder growth and development. Objective: To determine the relationship between low birth weight history (LBW) and stunting incidence in toddlers at Panggang 2 Gunungkidul Health Center. Method: The research method used is descriptive correlation analysis with cross-sectional design. The population in this study is 854 children under five years old as of 2023 with purposive sampling and 95 respondents. Bivariate data analysis using the Fisher Exact test. Results: The incidence of stunting in this study was only 28.4% and toddlers in the non-stunted category were 71.6%. The history of low birth weight in children aged 12-60 months is only a small part of 5.3% and most of them are included in the category of not having a history of low birth weight of 94.7% with a p-value of 0.022 (<0.05) and R-value of 0.260. Conclusion: There is a significant relationship between the history of low birth weight and the incidence of stunting in toddlers at the Panggang 2 Gunungkidul Health Center with a weak level of close relationship.